Efeito da densidade nutricional da dieta e suplementação com cromo nas concentrações séricas de glicose, insulina e ácidos graxos não esterificados em vacas de leite lactantes - Leiva, Tiago [UNESP] (2014)
The objective of this study was to evaluate the influence of energy density of the diet and chromium supplementation on serum concentrations of glucose, insulin, non-esterified fatty acids (NEFA) and IGF-1 in lactating dairy cows. Eighteen crossbred Holstein x Gir (DIM 76 ± 2) cows were allocated in two drylot pens and receiving free-choice of corn silage and water, they were separately by parturition (primiparous x multiparous) and milk yield, and randomly assigned to one of three treatments on d0 of the experiment: 1) CON: diet formulated to reach 100% of maintenance and lactation requirement, without chromium supplementation (n=5); 2) BPSC: diet formulated to reach 100% and 160% of the requirements for lactation and maintenance, respectively, without chromium supplementation (n=6); 3) BPCC: diet formulated to meet 100% and 160% of the requirements for lactation and maintenance requirements, respectively, with chromium supplementation (n=6; 2,5g of KemTRACETM Chromium Propionate 0,4% - Kemin Industries, Inc. - added in 97,5g of corn meal/animal/day). Blood samples were collected weekly for serum glucose, insulin and NEFA concentrations during the experiment (d0 to d210). Glucose Tolerance Tests (GTT) were performed each 42 days (d0, d42, d84, d126, d168, d210). During each GTT cows were infused (i.v.) with 0.5g of glucose/kg of body weight. Blood samples were collected at -15, 0, 10, 20, 30, 45, 60, 90 and 120 min relative to infusion. Ovarian pick-up was performed for oocyte quality and embryo production evaluation. There was no difference (P=0.74) in body weight during the study. Cows from the BPSC and BPCC groups had greater (P=0.02) Body Condition Score gain when compared to cows from the CON group. There was no...